Sit to Talk: Relation between Motor Skills and Language Development in Infancy - Libertus, Klaus; Violi, Dominic A. (Frontiers in Psychology, 2016)
Relations between walking skills and language development have been reported in 10- to 14-month-old infants. However, whether earlier emerging motor milestones also affect language skills remains unknown. The current research fills this gap by examining the relation between reaching and sitting skills and later language development respectively. Reaching and sitting were assessed eight times, starting when infants (N=29) were around three months of age. All assessments were completed and recorded remotely via videoconference using Skype or FaceTime. Subsequently, infants’ language and motor skills were assessed via parent questionnaires (Communicative Development Inventories and Early Motor Questionnaire) at 10 and 14 months of age. Results revealed a significant correlation between the emergence of sitting skills and receptive vocabulary size at 10 and 14 months of age. Regression analyses further confirmed this pattern and revealed that the emergence of sitting is a significant predictor of subsequent language development above and beyond influences of concurrent motor skills. These findings suggest that the onset of independent sitting may initiate a developmental cascade that results in increased language learning opportunities. Further, this study also demonstrates how infants’ early motor skills can be assessed remotely using videoconference.